TIPOLOGI SANTRI MASJID TIBAN SANANREJO - Sholah, Hanif Maulaniam; Ilmi Nikmatul Hikmah; Mufarrohah (LP3M IAI Al-Qolam, 2018)
Interesting Phenomenon in an Islamic place called ?Pondok Pesantren? which is located in Sananrejo village Turen district region of Malang attracts many attentions to a large of citizens. It is issued that the Pondok Pesantren which is well known with the term Pondok Pesantren Bih?r Bahr ?Asal Fadl?il al-Rahmah is a Mosque which is built by spirit where many people called them as ?Jin?. In this case, this research is eager to investigate the motivation which become the background of establishing the Pondok Pesantren, how the proses of constructing this huge building with eleven floors and more than one hectare area of building; how the belief and characters which is taught in this Pondok Pesantren; and how the typology as well as ideology of Santri in this Pondok Pesantren.  This research applies descriptive qualitative method by which the data collection is carried out using observation and interview. This also brings out phenomenology approach to reveal the ideology of the santris of Bih?r Bahr ?Asal Fadl?il al-Rahmah. Based on the result of observation and interview conducted and analyzed by the researcher, Santris of this Salaf? Pesantren which is often visited by many visitors, and even foreigners from any regions, show polite attitude. This behaviour has become the tradition and culturally implemented by all of Santris in this pesantren toward any visitors. Keywords: Typology, Santri, Pondok Pesantren